2013
DOI: 10.1111/pbi.12060
|View full text |Cite
|
Sign up to set email alerts
|

Engineering cherry rootstocks with resistance to Prunus necrotic ring spot virus through RNAi‐mediated silencing

Abstract: Summary Prunus necrotic ringspot virus (PNRSV) is a major pollen‐disseminated ilarvirus that adversely affects many Prunus species. In this study, an RNA interference (RNAi) vector pART27–PNRSV containing an inverted repeat (IR) region of PNRSV was transformed into two hybrid (triploid) cherry rootstocks, ‘Gisela 6’ (GI 148‐1) and ‘Gisela 7’(GI 148‐8)’, which are tolerant and sensitive, respectively, to PNRSV infection. One year after inoculation with PNRSV plus Prune Dwarf Virus, nontransgenic ‘Gisela 6’ exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 42 publications
0
43
0
Order By: Relevance
“…All NR/scion trees died within 3 years after inoculation with either CH39 or Fulton G, of which CH39 (a more virulent PNRSV isolate) caused tree death 1 year earlier than Fulton G. In contrast, for the TR/scion trees grafted onto transgenic rootstocks from seven independent transgenic events, all three trees were alive 3 years after the inoculation with the Fulton G and one (TR4/scion) of four TR/scion trees was alive after the inoculation with CH39 (Figure , Table ). The expression levels of the PNRSV‐hpRNA in different TR events could be responsible for the variations in PNRSV resistance among the TR/scion trees when challenged with CH39 (Song et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…All NR/scion trees died within 3 years after inoculation with either CH39 or Fulton G, of which CH39 (a more virulent PNRSV isolate) caused tree death 1 year earlier than Fulton G. In contrast, for the TR/scion trees grafted onto transgenic rootstocks from seven independent transgenic events, all three trees were alive 3 years after the inoculation with the Fulton G and one (TR4/scion) of four TR/scion trees was alive after the inoculation with CH39 (Figure , Table ). The expression levels of the PNRSV‐hpRNA in different TR events could be responsible for the variations in PNRSV resistance among the TR/scion trees when challenged with CH39 (Song et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Prunus necrotic ringspot virus (PNRSV) is a major pollendisseminated Ilarvirus that adversely affects many Prunus species (Barbara et al, 1978). In a previous study, we found that the siRNAs derived from a hairpin sequence of partial PNRSV coat protein (PNRSV-hpRNA) were extremely efficient in protecting transgenic cherry rootstocks (TRs) from PNRSV damage (Song et al, 2013). To investigate whether these siRNAs can be transferred and exert systemic silencing effect in nontransgenic scions, we conducted grafting experiments (cherry rootstock/ scion), sequenced and profiled PNRSV-specific siRNAs in the samples of 1) PNRSV-free and PNRSV-inoculated transgenic rootstocks (TRs); 2) PNRSV-free and PNRSV-inoculated sweet cherry trees grafted on nontransgenic rootstocks (NRs) (herein, NR/scion); and 3) PNRSV-free and PNRSV-inoculated sweet cherry trees grafted on TRs (herein, TR/scion).…”
Section: Introductionmentioning
confidence: 99%
“…The size of the inverted repeat regions of the sequence in RNAi vectors is an important factor to take into account when the objective is the transformation of Prunus species. Song et al . suggested that a vector with a shorter inverted repeat region is preferable to a vector containing a longer inverted repeat region for the generation of transgenic cherry plants.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that siRNAs are mobile silencing signals . Transgenic cherry rootstocks resistant to Prunus necrotic ringspot virus (PNRSV) have been obtained through RNAi‐mediated gene silencing . Subsequently, Zhao and Song demonstrated the transfer of transgene‐derived siRNAs from cherry transgenic rootstocks to non‐transgenic scions in grafted trees.…”
Section: Discussionmentioning
confidence: 99%
“…Rootstock transformation would be appealing, for several reasons: the scion would maintain its genetic background; no gene flow, because pollen and seeds would not be allowed to be produced by the genetically modified rootstock; the same transgenic rootstock can be used for many cultivars, avoiding the transformation of each single accession; and it may simplify many aspects related to the opinion of the consumers on GM plants (Lemgo et al, 2013). Recently, this approach has been successfully applied in a cherry rootstock to induce RNAi-mediated systemic resistance to Prunus Necrotic Ringspot Virus (Song et al, 2013; Zhao and Song, 2014), although the stability and durability of this approach requires further evaluation. On the contrary, transmission of RNA silencing was not observed in non-transgenic scions in apple (Flachowsky et al, 2012), and thus, additional research is required to set-up the appropriate strategies for an efficient silencing through grafting (Gohlke and Mosher, 2015).…”
Section: Introducing Resistance In Peach By Genetic Engineeringmentioning
confidence: 99%